2019
DOI: 10.1186/s13613-019-0571-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory failure and mechanical ventilation in cardiogenic shock complicating acute myocardial infarction in the USA, 2000–2014

Abstract: Background: There are limited epidemiological data on acute respiratory failure (ARF) in cardiogenic shock complicating acute myocardial infarction (AMI-CS). This study sought to evaluate the prevalence and outcomes of ARF in AMI-CS. Methods: This was a retrospective study of AMI-CS admissions during 2000-2014 from the National Inpatient Sample. Administrative codes for ARF and mechanical ventilation (MV) were used to define the cohorts of no ARF, ARF without MV and ARF with MV. Admissions with a secondary dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 39 publications
7
54
0
2
Order By: Relevance
“…During the period between 1 January 2000 through 31 December 2016, a retrospective cohort of admissions from the HCUP-NIS with a primary diagnosis of AMI (International Classification of Disease-9 Clinical Modification [ICD-9CM] 410.x; International Classification of Disease-10 Clinical Modification [ICD-10CM] I21.x-22.x) receiving ECMO support (ICD-9CM 39.65; ICD-10CM 5A15223) were identified consistent with prior literature [7]. Deyo's modification of Charlson Comorbidity Index was used to identify co-morbid diseases and prior methodology was used to identify cardiac and non-cardiac procedures [2,3,7,8,11,[13][14][15][16][17][18][19][20][21][22][23]. We identified relevant complications and categorized them as (a) vascular complications-arterial injury, acquired arterio-venous fistula, and vascular complications requiring surgery; (b) lower limb amputation; (c) hematologic-post-operative hemorrhage, hemolytic anemia, thrombocytopenia, and blood transfusion; and (d) neurologic-ischemic or hemorrhagic stroke ( Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the period between 1 January 2000 through 31 December 2016, a retrospective cohort of admissions from the HCUP-NIS with a primary diagnosis of AMI (International Classification of Disease-9 Clinical Modification [ICD-9CM] 410.x; International Classification of Disease-10 Clinical Modification [ICD-10CM] I21.x-22.x) receiving ECMO support (ICD-9CM 39.65; ICD-10CM 5A15223) were identified consistent with prior literature [7]. Deyo's modification of Charlson Comorbidity Index was used to identify co-morbid diseases and prior methodology was used to identify cardiac and non-cardiac procedures [2,3,7,8,11,[13][14][15][16][17][18][19][20][21][22][23]. We identified relevant complications and categorized them as (a) vascular complications-arterial injury, acquired arterio-venous fistula, and vascular complications requiring surgery; (b) lower limb amputation; (c) hematologic-post-operative hemorrhage, hemolytic anemia, thrombocytopenia, and blood transfusion; and (d) neurologic-ischemic or hemorrhagic stroke ( Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Extracorporeal membrane oxygenation (ECMO) is increasingly used in acute cardiovascular care for the management of acute myocardial infarction (AMI) complicated by cardiac arrest, cardiogenic shock and complications from cardiac interventional procedures [1][2][3][4][5][6][7][8][9][10]. ECMO provides cardiac output support of nearly 3-5 L, biventricular support and respiratory support, thereby assisting with critical cardiorespiratory support in extreme situations [11]. Despite limited data and the absence of randomized controlled trials, ECMO has been widely accepted in clinical practice [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The timing of in-hospital events, including IHD remains underexplored in critical illness [1,8,15]. In a nationally-representative population of STEMI admissions that received primary PCI, we previously demonstrated that ventricular arrhythmias were predominant in early in-hospital cardiac arrest, whereas non-shockable rhythms and multi-organ involvement were prevalent in the delayed group [13].…”
Section: Discussionmentioning
confidence: 99%
“…In AMI-CS, most mortality analyses and predictive models have used IHD, 28-day or 30-day mortality as the end-points, with little additional granularity on the timing of IHD during the index hospitalization [10]. Previous work from our group has demonstrated that AMI-CS patients frequently transition to invasive mechanical ventilation in the first two days, as well as a temporal decrease in the use of prolonged mechanical ventilation and tracheostomy use in the United States [15,20]. Taken in aggregate, these data might suggest that there have been improvements in care delivery for this acutely ill population, decreasing the burden of chronic critical illness [11].…”
Section: Discussionmentioning
confidence: 99%
“…The four geographic regions included the Northeast, Midwest, South, and West as classified by the HCUP‐NIS 35 . Similar to prior literature, we defined early coronary angiography as that performed on the day of hospital admission (day 0) 31,42,43 . We identified timing of coronary angiography and percutaneous coronary intervention (PCI) relative to the day of admission 18,31,41,42 …”
Section: Methodsmentioning
confidence: 99%